The role of intercultural communicative competence in the development of World Englishes and Lingua Francas - Houghton, Stephanie (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
There is a tendency to think of World Englishes in the noun form; as products rather than as processes (implying that one receives both ready-made, controlling the development of neither).Conceptualising World Englishes as processes in which one can participate as an agent raises the question of what skills are needed in their active construction. The author will argue that since culture resides partly in language, the development of intercultural communicative competence (Byram 1997) should play a pivotal role in foreign language education both to preserve cultural and linguistic diversity, facilitating and enhancing intercultural communication in the process. A range of skills considered central to intercultural communicative competence will be presented and illustrated showing how language students can learn to take control over the development not only of language, but of their own identities.